The Individualism and Collectivism Doctrine in Law and theirImpact on the Family - Mahmoud, Dr. Dlawar Saleh; Ismail, Omid Aziz (Journal of Legal and Political Studies, 2018)
The adoption of collectivism in Iraqi law and in the other countries was a result for the negative impact of the individualism over the society, especially, when the individualism led to inacceptable outcomes in the conservative societies. Though, individualism theory has obtained many human values and goals, the application of its tenets in realty will drive our societies to results which cannot be tolerated, such as, same-sex marriage and abortion, which they are legalized by American laws under the influence of individualism theory. In order to avoid such those negative effects, the Iraqi legislator has adopted collectivism, especially, in laws related to family.
Keywords: collectivism; conservative societies; individualism; Iraqi legislator